Preliminary evaluation of anatomical characteristics of four common Mongolian softwoods - Sarkhad, Murzabyek; Ishiguri, Futoshi; Nezu, Ikumi; Aiso, Haruna; Ngadianto, Agus; Tumenjargal, Bayasaa; Baasan, Bayartsetseg; Chultem, Ganbaatar; Ohshima, Jyunichi; Yokota, Shinso (2022)
To effectively and sustainably utilize wood resources from boreal forests in Mongolia, anatomical characteristics, tracheid morphology, cell proportion, annual ring width, and latewood percentage were preliminary determined in Pinus sylvestris, Pinus sibirica, Picea obovata, and Larix sibirica trees naturally growing in Mongolia. Based on the observation, the anatomical characteristics of four common Mongolian softwoods were the same as those previously observed in the same species or the same genus species. Based on the parameters of the Gompertz functions for annual ring width, silvicultural management, such as thinning timing and harvesting age, should be considered depending on the species when the plantation is established. The results of the model selection for relationships between latewood percentage and basic density indicated that the increase ratio of basic density corresponded to an increase of latewood percentage is almost the same irrespective of species, although there are species-specific values of basic density corresponding to specific latewood percentages. The results obtained in the present study contribute effective and sustainable utilization of wood resources from Mongolian forestry. © 2022 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.